Capturing and missing the patient's story through outcome measures : a thematic comparison of patient-generated items in PSYCHLOPS with CORE-OM and PHQ-9 - Sales, Célia M. D. (2017)
© 2017 The Authors Health Expectations Published by John Wiley & Sons Ltd. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.